Insider Trading: Should It Be Prohibited? - Leland, Hayne E. (Journal of Political Economy, 1992)
Insider trading moves forward the resolution of uncertainty. Using a rational expectations model with endogenous investment level, I show that, when insider trading is permitted, (i) stock prices better reflect information and will be higher on average, (ii) expected real investment will rise, (iii) markets are less liquid, (iv) owners of investment projects and insiders will benefit, and (v) outside investors and liquidity traders will be hurt. Total welfare may increase or decrease depending on the economic environment. Factors that favor the prohibition of insider trading are identified.